Aerobic High-Intensity Exercise Training Improves Cardiovascular Health in Older Post-menopausal Women - Hoier, Birgitte; Olsen, Line Nørregaard; Leinum, Maria; Jørgensen, Tue Smith; Carter, Howard Henry; Hellsten, Ylva; Bangsbo, Jens (Frontiers in Aging, 2021)
The aim of this study was to determine the effect of a period of aerobic high intensity training on central- and peripheral cardiovascular parameters in older postmenopausal women. Eleven healthy postmenopausal (>10 years after menopause) women (mean age: 64 years; BMI: 25.3 kg m-2) completed an 8-week period of supervised, high intensity cycle training, with sessions conducted three times per week. Before and after the training period maximal oxygen uptake, body composition, popliteal artery flow mediated dilation, exercise hyperemia, arterial blood pressure, and plasma lipids were assessed. In addition, levels of estrogen related receptor  (ERR) and vasodilator enzymes were determined in muscle biopsy samples. Training induced an 18% increase (P<0.001) in maximal oxygen uptake. Plasma High-density lipoprotein (HDL) was higher (P<0.05) after than before the training period. Fat mass was reduced (4.9%; P<0.01), whereas lean body mass was unaltered. Mean arterial blood pressure was unchanged (91 vs. 88 mmHg; P=0.058) with training. Training did not induce a change in popliteal flow mediated dilation. Exercise hyperemia at submaximal exercise was lower (P<0.01; 11 and 4.6% at 10 and 16W, respectively) after compared to before training. Muscle ERR (~1.7-fold; P<0.01) and eNOS (~1.4-fold; P<0.05) were higher after the training intervention. The current study demonstrates that, in older postmenopausal women, a period of aerobic high intensity training effectively increases maximal oxygen uptake and improves the cardiovascular health profile, without a parallel improvement in conduit artery function.